Protracted post-glacial hydrocarbon seepage in the Barents Sea revealed by U–Th dating of seep carbonates - Himmler, Tobias; Wagner, Doris; Sahy, Diana; Vadakkepuliyambatta, Sunil; Chand, Shyam; Martma, Tõnu; Kirsimäe, Kalle; Mattingsdal, Rune; Panieri, Giuliana; Bünz, Stefan; Condon, Daniel J.; Knies, Jochen; et al. (Frontiers in Earth Science, 2024)
The hydrocarbon seepage chronology during deglaciation across the formerly glaciated Barents Sea was established using uranium-thorium (U-Th) dating of seep carbonates. Seep carbonates were sampled with remotely operated vehicles (ROV) from the seafloor at three active hydrocarbon seeps (water depth 156 to 383 meters), located in the north-west (Storfjordrenna), north-central (Storbanken High), and south-west (Loppa High) Barents Sea. Overall, the U-Th dates range from 13.5 to 1.2 thousand years (ka) before present, indicating episodic seep carbonate formation since the late Pleistocene throughout the Holocene. The new U-Th dates indicate protracted post-glacial gas seepage, congruent with previously published seep carbonate ages from the south-west Barents Sea. Gas hydrate dissociation and associated seep carbonate formation occurred at Storfjordrenna between ≈6 and 1.2 ka, and around 13.5 and 6 ka at Storbanken. Early and late Holocene seep carbonate ages from Loppa High support post-glacial seismic activity as potential seepage trigger mechanism.